The Influence of Compensation, Motivation and Work Environment on Employee Performance : (Case Study on Sultan Agung Syariah Consumer Cooperative RSI Sultan Agung Semarang) - Lita Rustian; Misbakhul Munir; Tjandra Tirtono (Perspective Humanities and Social Sciences, 2025)
This study aims to determine the effect of compensation, motivation and work environment on employee performance at Kopmensa RS Sultan Agung Semarang. The type of research used is quantitative research with an ex post facto approach. The population in this study were all Kopmensa employees and the sample used was 75 employees using a sampling technique, namely simple random sampling. The data collection technique used a questionnaire. The data analysis technique used was Multiple Linear Regression. The results of the study partially showed that compensation (X1) and motivation (X2) had a positive and significant effect on employee performance (Y), while the work environment (X3) had no effect on employee performance (Y). Keywords : Performance, Compensation, Motivation, Work Environment